(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Consciousness as one of the main factor of personality influences on job satisfaction of academic staff and both of these factors assumed as important factors in university. Indeed, level of job satisfaction depends on personality characteristic of academic staff at work. The central purpose of current study was to investigating role of emotional intelligence as mediator factor between consciousness and job satisfaction among 440 academic staff in public research universities. Instruments used to collect data were Job Descriptive Index, Big Five Inventory and Emotional Intelligence Inventory. Descriptive and inferential statistic was used to analyze the data and also SEM applied for illustrated role of mediator factor between consciousness and job satisfaction. The results of present study shown that among factors of emotional intelligence, utilization mediates relationship between consciousness and job satisfaction. Certainly, these results have significant implication on the policies universities specially universities in Malaysia.Consciousness as one of the main factor of personality influences on job satisfaction of academic staff and both of these factors assumed as important factors in university. Indeed, level of job satisfaction depends on personality characteristic of academic staff at work. The central purpose of current study was to investigating role of emotional intelligence as mediator factor between consciousness and job satisfaction among 440 academic staff in public research universities. Instruments used to collect data were Job Descriptive Index, Big Five Inventory and Emotional Intelligence Inventory. Descriptive and inferential statistic was used to analyze the data and also SEM applied for illustrated role of mediator factor between consciousness and job satisfaction. The results of present study shown that among factors of emotional intelligence, utilization mediates relationship between consciousness and job satisfaction. Certainly, these results have significant implication on the policies universities specially universities in Malaysia.